Al alloy/Ti3SiC2 composites fabricated by pressureless infiltration with melt-spun Al alloy ribbons. Issue 6 (15th April 2018) - Zhou, Chaolan; Wu, Xiaoyu; Ngai, Tungwai L.; Li, Liejun; Ngai, Sieglind; Chen, Zimo
Abstract: Al alloy/Ti3 SiC2 composites with compressive strengths ranging from 743 to 932 MPa have been successfully fabricated by a new two-step pressureless infiltration method. 6061 Al alloy ribbons prepared by melt spinning were employed as the Al alloy matrix for melt infiltration. Shifts in phase constitution and reaction mechanisms of Ti3 SiC2 preforms in molten Al at 950 °C were investigated, and the compression performance of Al alloy/Ti3 SiC2 composites was tested. The Vickers hardness of the composites was enhanced to a maximum of 751 HV by increasing the Al content.